Kritik Kepemimpinan Nadhiem Makariem Terhadap Kurikulum Merdeka - Sukataman, Sukataman; Wardhani, Sayekti Putri; Musyaffa, Kaifa Baits; Alfiyah, Siti (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
Leadership is basically a person’s ability to influence others, leadershipis the same as a nature, being a leader is a choice, but everyone must have a leadership spirit. Indeed, leadership is a characteristic and a style of a leader, meaning that every human being is a leader, et least someone leads himself in organizing and the machanism of his life. Leadership is an important for a capital policy holder such as the chairman, director, president and ministrerial ranks. Being the leader of an institution forces a person to always be the focus of the public (public figure). Nadhiem Makariem became an Indonesian public figure when he was appointed Minister of Education, Culture, Research and Technology. Pros and cond responses are a phenomenome that often comes to Nadhiem Makariems leadership style and policies. Therefore, this paper will present a response in the form of a critique of Nadhiem Makariem’s leadership style and policies. The method used by the autor is a qualitative appoarch using interview techniuqes, literature and research and references that allude to Nadhiem Makariem’s policies and leadership style. From some of the processing of the data obtained, the autor gives the title “Nadhiem Makariem’s Leadership Criticsm of the Kurikulum Merdeka”. The autors hopes that this paper can provide an understanding of the leadership style and policies set by the goverment.